2022
DOI: 10.3390/plants11152059
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Tolerance to Salt Stress and Water Deficit in Two Invasive Weeds of the Genus Erigeron (Asteraceae)

Abstract: Erigeron bonariensis and E. sumatrensis are two noxious weeds present in many parts of the world. Their tolerance to salinity and water deficit was analysed at the seed germination stage and during vegetative development. Seed germination was tested in solutions with different concentrations of NaCl and polyethylene glycol (PEG). Growth parameters, photosynthetic pigments, ion accumulation, and antioxidant mechanisms were analysed in plants that were subjected to increasing NaCl solutions, or severe water defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
1
3
0
Order By: Relevance
“…The seeds of the two species germinated at a different rate, with C. sumatrensis being the faster one. The highest percentage of seed germination for C. sumatrensis was absolutely comparable to the one mentioned by Bellache et al [10]. Under low drought stress (−0.2 MPa), the resistant biotype of C. sumatrensis had significantly higher germination percentage than the susceptible biotype.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The seeds of the two species germinated at a different rate, with C. sumatrensis being the faster one. The highest percentage of seed germination for C. sumatrensis was absolutely comparable to the one mentioned by Bellache et al [10]. Under low drought stress (−0.2 MPa), the resistant biotype of C. sumatrensis had significantly higher germination percentage than the susceptible biotype.…”
Section: Discussionsupporting
confidence: 84%
“…On the contrary, many weeds also show such ability, allowing us even to predict future shifts of specific species, dispersal of invasive species and changes in weed communities [9]. This is also the case for Conyza (Erigeron) species, since they are very often exposed to severe drought and other extreme environmental conditions and consequently any plasticity and adaptation would be beneficial for them [10].…”
Section: Introductionmentioning
confidence: 99%
“…The major phenolic compounds found in the stevia leaves are hydroxycinnamic acid and quinic acid, characterised with valuable therapeutic properties [3]. General studies about a variety of different plants, mostly from the Asteraceae family, have shown that increases in the production of various phenolic compounds is a typical response of many of the plant species to drought stress; therefore, it is not surprising to see these results in the studies about Stevia rebaudiana plants [31][32][33].…”
Section: Dry Mass Content and Concentration Of Reducing Sugars Phenol...mentioning
confidence: 99%
“…Another trait of invasive plants is their increased phenotypic plasticity, which generally gives them a greater fitness advantage 8 . The significance of climate change's effects on biological invasions is reflected in an increasing number of studies on invasive species' responses to abiotic stress under different experimental conditions 9 11 and comparative studies of functional traits in invasive and native species 2 , 12 , 13 . However, a binary classification into invasive and non-invasive ornamentals is problematic since invasiveness is not discrete, and species can be native to one place but invasive to another 14 .…”
Section: Introductionmentioning
confidence: 99%